2021
DOI: 10.1002/saj2.20225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating three calibration transfer methods for predictions of soil properties using mid‐infrared spectroscopy

Abstract: Mid-infrared (MIR) spectroscopy models have been developed for rapid assessment of soils but are often soil and instrument specific because of differences in laboratory conditions and sensor setup. Calibration transfer is required to apply a spectral model such as partial least squares (PLS) regression developed from a primary instrument to a spectral dataset measured by a secondary instrument with statistically retained accuracy and precision. The study aimed to compare the performance of three transfer metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 57 publications
4
17
0
Order By: Relevance
“…A more detailed description of the calibration transfer techniques can be found in Pittaki‐Chrysodonta et al. (2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed description of the calibration transfer techniques can be found in Pittaki‐Chrysodonta et al. (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Spectral preprocessing techniques can minimize the differences between different scanning environments (Kramer et al., 2008) and have been shown to be effective in a study exploring the use of a large MIR spectral library on a different instrument (Seybold et al., 2019). However, calibration transfer, where a set of common samples are scanned on both instruments and a transfer function is developed, is often necessary for improving predictions (Dangal & Sanderman, 2020; Ge et al., 2011; Pittaki‐Chrysodonta et al., 2021). The main drawback of calibration transfer is the need to share a common set of soils across instruments.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important finding and warrants further investigation into the causes of the bias, especially at low SOC values, and into ways of overcoming the bias. Other calibration transfer approaches such as spectral space transformation might overcome this issue [18].…”
Section: How Well Can Spectroscopy Predict Soil Organic Carbon?mentioning
confidence: 99%
“…Building large training sets with high quality laboratory data associated with the spectra, such as in the studies listed above, is not an option available to most analytical labs. There is growing interest in applying predictive models built on these large libraries to spectra acquired on other instruments [17,18]. Due to differences in instrument configuration and environmental conditions during spectral acquisition, variations in spectra will arise.…”
Section: Introductionmentioning
confidence: 99%
“…Dangal and Sanderman [18] and Sanderman et al [19] showed that applying a calibration transfer function (TF) to the SSLs in question enabled the merging of two SSLs from readings obtained by two diferent spectrometers. Moreover, Pittaki-Chrysodonta et al [20] recently suggested that the spectral TF idea could be more efcient at minimizing the root mean square error (RMSE) in the spectral assessment of soil properties. It is interesting to note that Francos and Ben-Dor [21] presented a TF concept based on a random forest (RF) [22] algorithm to predict soil surface refectance in the feld using laboratory spectral measurements of Mediterranean soils from diferent countries (Italy, Israel, and Greece).…”
Section: Introductionmentioning
confidence: 99%